Relationship Parental Social Support and Subjective Well-Being In Adolescents - Febi Mariana Tefbana; M. Dinah Charlota Lerik; Yeni Damayanti (Journal of Health and Behavioral Science, 2021)
Abstract. Human beings certainly want happiness in life, because happiness is something important and must be achieved by each individual because it is individual. Subjective well-being is felt and experienced by everyone, including teenagers. Adolescence is a stage of development where individuals undergo a transition from childhood to adulthood. A very important factor in the subjective well-being experienced by adolescents is social support. Social support is a feeling of comfort, attention, and respect that is received by individuals from other individuals or groups. This research is quantitative research, with the method used is a correlation study. The sampling technique is using random stratification with the number of samples in this study as many as 90 people. The subjects in this study were adolescents. Data analysis using Pearson Product Moment correlation test. Test results between social support parents and subjective Well-Being -0.516, there is a positive and significant relationship between the two research variables. The higher the social support of parents felt by teenagers, the higher the subjective well-being in the teenagers of SMA Negeri Banat.